Kriptografi dan Steganografi Penyembunyian Pesan Pada Media Audio Menggunakan Algoritma AES - Lambok Hasudungan Sijabat; Nenna Irsa Syahputri; Mufida Khairani (ALGORITMA : JURNAL ILMU KOMPUTER DAN INFORMATIKA, 2021)
Cryptography can be used to process messages with certain algorithms so that the meaning of the message is difficult to understand. After that, steganography was used to hide messages in other forms. This study uses AES and Least Significant Bit (LSB) to build desktop-based applications using VB to send messages and get original messages. This application itself will concentrate the application of dual security for data and use WMA audio files to strengthen security on text data owned by users. Conceptually, security will be carried out by first encrypting messages using AES cryptography and then continuing the second security process by inserting text data in the WMA Audio file using the LSB algorithm to prevent indication or suspicion of the existence of important data or information that is inserted in the data.Keywords : Cryptography, Steganography, AES, LSB